'Legal highs': Novel psychoactive substances. Issue 12 (December 2015) - Gilani, Farah
Amid increasing media attention, 'legal highs' pose a novel diagnostic and management challenge to clinicians. The manufacture, propagation and use of these drugs are increasing rapidly. However, knowledge of their composition and the consequences of taking them is limited, both among the public and health professionals. This article will focus on those drugs that are still currently available legally, their classification, management and the role of the GP in identifying users, and managing and referring them appropriately.